Association of the level of cognition and obesity among middle-aged adults in Sri Lanka - Ariyasinghe, Pushpika; Kumara, Ruwan; Alexander, Dham; Senarathna, Harsha; Kasthuri, Sunethra; Galgamuwa, Lahiru Sandaruwan; Karunathilaka, Nimantha; Warnakulasuriya, Sudath (International Journal of Research in Medical Sciences, 2021)
Background: Cognition is the collection of an intellectual process, such as perception, thinking, and reasoning for goal-directed behaviours. The obesity-associated cognitive functions (CFs) was varied due to inconsistency of the findings and it is also context bounded. The objective was to assess the association between cognitive function and obesity among middle-aged adults in Sri Lanka. Methods: A descriptive study was conducted among middle-aged adults aged between 50-60 years in Colombo District, Sri Lanka. While Generalized obesity was estimated by the WHO cutoff of body mass index (BMI) while the central obesity was determined using and waist hip ratio (WHR). CFs was assessed using a validated Montreal cognitive assessment (MoCA) and the Mini-mental state examination (MMSE) tools. Results: The study sample consisted of 83 subjects of each obese and normal weight categories, while 50% were females. Middle-aged adults with obesity showed significantly lower CF scores in both MoCA and MMSE compared to the normal-weight adults (p<0.01). In addition, lower MMSE scores were significantly associated with high WHR values (p<0.05). The level of education of adults was a significant predictor of cognitive functions among middle-aged adults (p<0.05). Conclusions: Therefore, the results further confirmed that obesity-associated cognitive impairment among middle-aged adults and further research is warranted to clarify the cause and effect relationship between obesity and body composition.